The effects of transgenic melanocortin overexpression in atherosclerotic mice - Nuutinen, Salla (fi=Turun yliopisto|en=University of Turku|, 2016)
Atherosclerosis is a chronic inflammatory disease of the arteries and a common cause of death worldwide. The disease is initiated by endothelial dysfunction that allows the transport of leukocytes and low-density lipoprotein (LDL) into the vessel wall where they form plaques. They impair the normal function of an artery. The melanocortin system is an endogenous modulatory system consisting of α-, β- and γ-melanocyte-stimulating hormones (α-, β- and γ-MSH), and corticotropin (ACTH); five melanocortin receptors, named MC1R-MC5R; and their antagonists, agouti and agouti-related peptide. Short-term melanocortin treatment alleviates vascular inflammation and dysfunction in atherosclerosis but, for now, no study has evaluated the long-term effects of the melanocortin system activation on atherosclerosis progression. The aim of this study was to evaluate the effects of the transgenic melanocortin system activation in a mouse model of atherosclerosis. It was hypothesised that trangenic overexpression of the melanocortin peptides limits the progression of atherosclerosis. Low-density lipoprotein receptor-deficient (Ldlr-/-) mice overexpressing α- and γ -MSH 3and their wildtype Ldlr-/- controls were fed either a regular CRM diet or high-fat and sugar Western-style diet for 16 weeks. During this time, their body weight and food consumption were monitored weekly. After the diet intervention, the aortae were collected for ex vivo wire-myograph analysis of the functional and mechanical properties of the aorta. In addition, the plaques in the aortic root and arch were characterised by histological and immunohistochemical stainings, and the expressions of inflammatory mediators were studied by reverse-transcription polymerase chain reaction (RT-qPCR). We found that on Western diet the melanocortin overexpression limited the plaque formation in the aortic arch and the expression of inflammatory cytokines (Ccl2, Ccl5 and Il6) that contribute to the pathogenesis of atherosclerosis. In addition, the melanocortin overexpression alleviated the α -adrenoceptor-mediated vasoconstriction 1and enhanced the endothelium-dependent dilation. Thus, the transgenic melanocortin overexpression improved the function of the aorta. These results show for the first time that the transgenic activation of the melanocortin system limits the progression of atherosclerosis by alleviating inflammation, plaque formation and arterial dysfunction.